Roles of CircRNAs in Autoimmune Diseases - Xia, Xin; Tang, Xinyi; Wang, Shengjun (Frontiers in Immunology, 2019)
Circular RNAs (circRNAs) are covalently linked single-stranded RNAs, compared to linear counterparts, that are relatively abundant, conserved, stable and specific. Previously, most studies have revealed that circRNAs function in gene expression processes and participate in the pathogenesis of cancers, cardiovascular diseases and neurological diseases. With advances in biotechnology, more biological functions of circRNAs have been found in several signaling pathways that are related to tumorigenesis, immunity and metabolism. Recently, many circRNAs have been reported to be expressed abnormally and play important roles in the progression of autoimmune diseases. Thus, circRNAs may not only serve as potential biomarkers but also act as immune regulators and offer potential opportunities for therapy. This review briefly introduces the properties as well as the functions of circRNAs in different stages of gene expression. In addition, this article summarizes the available knowledge about abnormally expressed circRNAs in different autoimmune diseases and discusses their potential roles in these diseases, which helps us understand their regulatory mechanisms and provides future research perspectives.